Unveiling Resistance and Virulence Mechanisms under Darwinian Positive Selection for Novel Drug Discovery for Gardnerella vaginalis - Eduarda Guimarães Sousa; Andrei Giacchetto Felice; Fabiana Vieira Dominici; Arun Kumar Jaiswal; Mariana Letícia Costa Pedrosa; Luiza Pereira Reis; Lucas Gabriel Rodrigues Gomes; Vasco Ariston de Carvalho Azevedo; Siomar de Castro Soares (Venereology)
Gardnerella vaginalis is a Gram-variable bacillus capable of causing bacterial vaginosis, a condition prevalent in reproductive-age women, this bacterium is present in almost 100% of cases and is also considered a gateway to various sexually transmitted infections. This organism exhibits high pathogenicity linked to virulence and resistance genes acquired throughout evolution, showcasing elevated resistance to a broad spectrum of drug classes. This study conducted comparative genomic analyses to identify these genes and correlate their presence with positive Darwinian selection. Additionally, new drug targets were selected through docking and molecular modeling, guided by the heightened antimicrobial resistance exhibited by this microbial species. The available genomes of G. vaginalis were analyzed, and the orthologous genes were delineated and positively selected, whereby 29 groups were found. Of these genes, one of great importance was predicted, Mef(A), which is related to resistance to the macrolide group of antibiotics, which are one of the main choices for the treatment of sexually transmitted infections. Additionally, two potential protein candidates were selected as drug targets. These proteins were linked with a natural compound each and are considered good potential drug targets. The analyses in this study contribute to analyzing the evolution of the species and how resistance genes are related to their permanence as a potential pathogen.